Innovation Success in the European Union: Aggregate Demand Analysis - Vaníček, Bernard; Fišera, Tomáš (Academic Conferences and Publishing International Limited, 2024)
In the current period of uncertainty in the European Union, innovation is becoming a key factor for maintaining not only economic stability but also competitiveness in the globalised environment. Following the financial crisis that hit Europe, aggregate demand indicators slowly started to stabilise, mostly reaching their peak in 2019. However, in the following year, due to the pandemic crisis, these indicators fell again, posing a new challenge for researchers around the world. This study examines the relationship between macroeconomic indicators of aggregate demand and innovation performance in 25 EU countries. Using data for the period 2013-2021 as input for the regression analysis, the research identifies firm investment and exports as important innovation support factors and highlights their key role. On the other hand, the research shows that household consumption and imports are barriers to innovation. Somewhat surprisingly, government spending on goods and services does not have a significant impact on innovation success, underlining the need to rethink government investment policies. This finding highlights the need for a more thorough analysis of the effectiveness of state investment in innovation and possible adjustments to state policies to maximise the promotion of innovation activities in the state. The study also highlights the importance of comprehensive strategies that promote investment and exports, while emphasising the removal of barriers to innovation in the form of household consumption and imports.
Úspěch inovací v Evropské unii: Analýza agregátní poptávky
Keywords: innovation success; aggregate demand; investment; export; import; inovační úspěch; agregátní poptávka; investice; export; import